Regularization Approach for Network Modeling of German Energy Market - Shi Chen; Wolfgang Karl Härdle; Brenda López Cabrera (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2018)
We investigate the concept of connectedness, which is important for risk measurement and management inGerman energy market. Understanding and learning from these mechanisms are essential to avoid future systemic disasters. To deal with large portfolio selection, we propose regularization approach to capture the spillover and contagion effects acrossGerman power derivatives. This paper shows how network analysis can facilitate the monitoring of futures price movements. Our methodology combines high-dimensional variable selection techniques with network analysis, the results show that contracts like Phelix Base Year Options and Phelix Peak Year Futures are in the core of the Energy futures market.
Keywords: C1; Q41; Q47; 330; regularization; energy risk transmission; network; German energy market